2 Predicting abdominal aortic aneurysm growth using 18F-sodium fluoride PET-CT. (May 2018) - Forsythe, Rachael O; Dweck, Marc R; McBride, Olivia MB; Vesey, Alex T; Semple, Scott I; Shah, Anoop SV; Adamson, Philip; Wallace, William; Kaczynski, Jakub; van Beek, Edwin JR; D Gray, Calum; Fletcher, Alison; et al.
Abstract : Introduction: Abdominal aortic aneurysm (AAA) growth is non-linear, yet surveillance relies on ultrasound-derived measures of diameter to predict future growth. Biology plays a key part in aneurysm evolution but is not routinely assessed. 18 F-Sodium Fluoride ( 18 F-NaF) PET-CT identifies active vascular calcification associated with high-risk atherosclerotic plaque. In patients with AAA, we evaluated the use of 18 F-NaF PET-CT to predict aneurysm growth and outcomes. Methods: In prospective case-control (n=20 per group) and longitudinal cohort studies (patients with AAA ≥4 cm, n=72), subjects underwent ultrasound, 18 F-NaF PET-CT, CT angiography and calcium scoring. Endpoints were aneurysm expansion and AAA repair or rupture. Results: Higher uptake of 18 F-NaF was observed in AAA vs nonaneurysmal aorta within the same subjects (p=0.004) and aortas of control subjects (p=0.023). 18 F-NaF uptake localised to areas of aneurysm disease and active calcification on histology and micro-PET-CT. In the cohort study of predominantly elderly (mean age 73) men (85%), there were 19 AAA repairs (26.4%) and 3 ruptures (4.2%) after 510±196 days. Aneurysms in the highest tertile of 18 F-NaF uptake expanded 2.5 times more rapidly than those in the lowest tertile (3.10 [IQR 2.34–5.92 mm/yr] vs 1.24 [IQR 0.52 to 2.92 mm/yr]; p=0.008) and were almost 3 times more likely to rupture or be repaired (15.3% vs 5.6%; log-rank p=0.043), even when adjusted for aneurysm diameter. Agatston score was not associated with future growth or clinical events. Conclusion: 18 F-NaF uptake is an independent predictor of AAA growth. This is a novel and promising approach to the identification of disease activity in patients with AAA.